Evaluation of Mobile Learning Technology Usage in Education During the Pandemic - Normalasarie, Normalasarie (Universitas Nurul Jadid Probolinggo, Indonesia, 2023)
This study aims to evaluate the use of mobile learning (m-learning) technology in the educational process at SDN Benua Anyar 1 Banjarmasin, focusing on student engagement, satisfaction, and the challenges faced by educators. Using a qualitative approach, the study involves 20 students and 15 educators as subjects. Data were collected through in-depth interviews and observations of the learning process, and analyzed using thematic analysis to identify patterns and key issues. The findings indicate that m-learning enhances student engagement due to its flexible access, but does not show a significant difference in academic outcomes compared to traditional face-to-face learning. Additionally, issues such as unstable internet connections, device limitations, and lack of social interaction impact motivation and learning outcomes. These findings highlight the need for improvements in technological infrastructure and an approach that integrates social elements to enhance the effectiveness of m-learning.